Differential gene expression analysis identified determinants of cell fate plasticity during radiation-induced regeneration in Drosophila. - Michelle Ledru; Caitlin A Clark; Jeremy Brown; Shilpi Verghese; Sarah Ferrara; Andrew Goodspeed; Tin Tin Su (PLoS Genetics)
Ionizing radiation (IR) is used to treat half of all cancer patients because of its ability to kill cells. IR, however, can induce stem cell-like properties in non-stem cancer cells, potentiating tumor regrowth and reduced therapeutic success. We identified previously a subpopulation of cells in Drosophila larval wing discs that exhibit IR-induced stem cell-like properties. These cells reside in the future wing hinge, are resistant to IR-induced apoptosis, and are capable of translocating, changing fate, and participating in regenerating the pouch that suffers more IR-induced apoptosis. We used here a combination of lineage tracing, FACS-sorting of cells that change fate, genome-wide RNAseq, and functional testing of 42 genes, to identify two key changes that are required cell-autonomously for IR-induced hinge-to-pouch fate change: (1) repression of hinge determinants Wg (Drosophila Wnt1) and conserved zinc-finger transcription factor Zfh2 and (2) upregulation of three ribosome biogenesis factors. Additional data indicate a role for Myc, a transcriptional activator of ribosome biogenesis genes, in the process. These results provide a molecular understanding of IR-induced cell fate plasticity that may be leveraged to improve radiation therapy.